PENGARUH CITRA MEREK, LABELISASI HALAL, DAN KESADARAN HALAL TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK HALAL OLEH GENERASI Z - Jannah, Hanifah Ni'matul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to determine the influence of brand image, halal labeling, and halal awareness on the decision to purchase halal cosmetics by Generation Z in Malang City. This research uses a quantitative approach with a binary logistic regression analysis model, primary data from distributing questionnaires to 96 Generation Z respondents in Malang City. The results of the analysis show that simultaneously, the variables brand image, halal labeling, and halal awareness have a significant positive influence on the decision to purchase halal cosmetics. Partially, brand image and halal awareness have a significant positive influence, with odds ratio values ​​of 1.539 and 2.020 respectively. The halal labeling has no significant effect, even though the odds ratio value is 1.428. It is hoped that this research can become a reference for the government to simplify halal certification procedures and strengthen cooperation with BPOM. Apart from that, this research can be a reference for halal cosmetics manufacturers to ensure that the products they distribute to the public are certified halal.